Dictionary of IT terms - Sourie, Margaret; Kaushik, Sanjay (New Delhi Pentagon Press, 2001)
Dictionary of IT terms provides completes indexing to key computer and information technology related terms.The dictionary of IT terms is compiled for those who demand immediate access to authoritative explanations to more than 999 key cyberspace words, p
Keywords: Information technology-Dictionaries; Encyclopedias and dictionaries